2011
DOI: 10.1007/jhep10(2011)135
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of the SO(10) symmetry breaking vacua in the matrix model for type IIB superstrings

Abstract: We study the properties of the space-time that emerges dynamically from the matrix model for type IIB superstrings in ten dimensions. We calculate the free energy and the extent of space-time using the Gaussian expansion method up to the third order. Unlike previous works, we study the SO(d) symmetric vacua with all possible values of d within the range 2 ≤ d ≤ 7, and observe clear indication of plateaus in the parameter space of the Gaussian action, which is crucial for the results to be reliable. The obtaine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
80
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 48 publications
(90 citation statements)
references
References 39 publications
8
80
0
Order By: Relevance
“…Moreover, the extent of space-time in the extended d directions and that in the shrunken (10 − d) directions turn out to have a finite ratio even in the large-N limit. 4 While these results reveal interesting dynamical properties of the Euclidean model, the connection to our real space-time is not very clear. This motivated us to consider the Lorentzian model.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Moreover, the extent of space-time in the extended d directions and that in the shrunken (10 − d) directions turn out to have a finite ratio even in the large-N limit. 4 While these results reveal interesting dynamical properties of the Euclidean model, the connection to our real space-time is not very clear. This motivated us to consider the Lorentzian model.…”
Section: Introductionmentioning
confidence: 87%
“…Therefore, it is possible that a four-dimensional space-time is generated dynamically in this model. This issue has been studied in the Euclidean version of the model, 3,4,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] which can be obtained from (1) by making a Wick rotation…”
Section: Previous Work On Type Iib Matrix Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…First in the Euclidean model, it was found that SSB indeed occurs, but the SO(10) symmetry is broken down to SO(3) [9]. The extent of space-time in the extended direction and that in the shrunken direction are calculated, and their ratio is found to be around five in the large-N limit.…”
mentioning
confidence: 97%
“…1 we show the most recent results [9] based on the Gaussian expansion method [18] in the large-N limit. On the left we plot the free energy for the SO(d) symmetric vacuum.…”
Section: Euclidean Type Iib Matrix Modelmentioning
confidence: 99%